Family resilience, social support, and family coherence among Jewish, Muslim, and Druze widows who lost their spouses to sudden death. Issue 2 (7th February 2023) - Khatib, Anwar; Laufer, Avital; Finkelstein, Michal
Abstract: In this cross-sectional study, regressions and multivariate analyses of covariance were used to assess group differences regarding family resilience, family coherence, and social support among 184 widows from three cultural groups in Israel: Druze ( n  = 66), Jewish ( n  = 59), and Muslim ( n  = 59). Druze widows had the lowest social support, but no differences were found between groups regarding family resilience or family coherence. Social support was positively associated with education and living in a city, beyond group. Social support and family coherence were positively associated with family resilience, beyond group. The discussion addresses cultural changes among the three groups.